Precision medicine: a revolutionary trans-disciplinary field - Amaral, Olga (2022)
The advances in molecular biology and biotechnology, applied to human diseases, have allowed the rise of precision medicine. New approaches to medical diagnostics and care are now becoming a reality with precision healthcare. For years, diagnostics were based on clinical findings followed by strenuous work in the laboratory. The detective work of health professionals could take many years until a diagnostic was achieved and in the meantime the patients were degenerating with devastating disease.